THERMAL POST—BUCKLING OF AN ELASTIC BEAMS SUBJECTED TO A TRANSVERSELY NON—UNIFORM TEMPERATURE RISING - 李世荣 程昌钧 周又和 (Applied mathematics and mechanics, 2003)
Based on the nonlinear geometric theory of axially extensible beams and by using the shooting method,the thermal post-buckling responses of an elastic beams,with immovably simply supported ends and subjected to a transversely non-uniformly distributed temperature rising,were investigated.Especially,the influences of the transverse temperature change on the thermal psot-buckling deformations were examined and the corresponding characteristic curves were poltted.The numerical results show that the equilibrium paths of the beam are similar to what of an initially deformed beam because of the thermal bending moment produced in the beam by the transverse temperature change.